A study on machine learning methods for accuracy improvement of in-body device localization - Dmitrieva, Daria; Anzai, Daisuke; Kirchner, Jens; Fischer, Georg; Wang, Jianqing (BIOEM The Joint Annual Meeting of the Bioelectromagnetics Society and the European Bioelectromagnetics Association, 2022)
Wireless devices for medical purposes play a promising role in implant body area networks. This study presented an artificial intelligence-based method to improve the localization of the wireless capsule endoscope during the liquid phantom experiment. The channel characteristics of signal at 400 MHz medical implant communication service (MICS) band were calculated based on the experimental data and used for conventional maximum likelihood estimation as well as to simulate the synthetic training data to introduce a possible solution for training data harvesting. The proposed method showed the root mean square localization error of 1.74 cm compared with 6.66 cm of the conventional method <
Keywords: Body Area networks; BAN; implant communication; MICS

A Study on Neural Network Method for In-body Implantable Device Localization - Dmitrieva, Daria; Anzai, Daisuke; Kirchner, Jens; Fischer, Georg; Wang, Jianqing (IEICE Society conference, 2022)
Keywords: WCE; localization; RSSI; implant; ML; phantom